2005
DOI: 10.1038/sj.eye.6702159
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy: a training dilemma

Abstract: Aim/Purpose The incidence of trabeculectomy is falling due to more effective medical therapies, resulting in fewer trabeculectomy operations carried out by Ophthalmology trainees. This study audits all primary trabeculectomy procedures performed publicly at the two major teaching hospitals in Brisbane, Australia. Method A retrospective consecutive case review analysing the rates and outcomes of Ophthalmology trainee versus consultant trabeculectomies that were performed during the period May 1996-May 2002. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…17 In our study, consultants operated on significantly more cases of complicated glaucoma and those who had undergone previous ocular surgery. The only significant difference in IOP control was found at postoperative visit 1 month in trainee cases of pseudoexfoliation and lowtension glaucoma, in which IOP was significantly higher compared with consultant cases.…”
Section: Discussionmentioning
confidence: 66%
“…17 In our study, consultants operated on significantly more cases of complicated glaucoma and those who had undergone previous ocular surgery. The only significant difference in IOP control was found at postoperative visit 1 month in trainee cases of pseudoexfoliation and lowtension glaucoma, in which IOP was significantly higher compared with consultant cases.…”
Section: Discussionmentioning
confidence: 66%
“…Even without any pressure from subconjunctival air, early- and late-onset bleb leak and its associated hypotony are among the most common complications after trabeculectomy [5, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…City Eye Centre, Brisbane, Queensland, Australia E-mail: eye@cityeye.com.au Sir, Awareness and the use of nutritional supplementation for age-related macular degeneration patients We read with interest the article 'Awareness and the use of nutritional supplementation for age-related macular degeneration (AMD) patients' by Waisbourd et al 1 The authors reported that their 'AMD patients lack knowledge about their own ocular disease.' The authors, however, erroneously stated that 'other studies conducted internationally demonstrated lack of awareness for this blinding disease among the general population with 9.2-30% who were not familiar with the disease.'…”
Section: Ga Lee and R Troubeckmentioning
confidence: 99%